IMPROVING STUDENT LEARNING OUTCOMES IN THE FIELD OF STUDY INDONESIAN THROUGH THE PROBLEM SOLVING METHOD IN GRADE IV STUDENTS OF SDN 173456 HUTAGINJANG - Leben Panggabean,; Sinaga, Sannur (Jurnal Review Pendidikan dan Pengajaran, 2025)
The objectives of this study are to improve (1) the quality of the learning process for Indonesian Grade IV students of SD N 173456 Hutaginjang for the 2020/2021 Academic Year through the Problem-Solving method and (2) the quality of learning outcomes for Indonesian Grade IV students of SD N 173456 Hutaginjang for the 2020/2021 Academic Year through the Problem-Solving method. This research is in the form of Classroom Action Research (PTK). The research object is Indonesian learning, while the research subject is Grade IV students of SD N 173456 Hutaginjang for the 2020/2021 academic year, totaling 24 students. The data sources used are documents, informants, and event venues. This research was carried out in two cycles. Based on the study's results, it can be concluded that (1) The Problem-Solving Method can improve the quality of the learning process for Indonesian Grade IV students of SD N 173456 Hutaginjang for the 2020/2021 Academic Year. This is shown by the percentage of student activity and seriousness in learning Indonesian, which has increased each cycle. There was an increase of 25% in the completeness of Indonesian learning outcomes, from 70% in the first cycle to 95% in the second cycle. This shows that the Problem-Solving learning method can improve Indonesian learning outcomes. (2) The Problem-Solving method can improve the quality of learning outcomes for Indonesian Grade IV students of SD N 173456 Hutaginjang for the 2020/2021 Academic Year.